Law no 76 of the year 2016 on amending certain provisions of law no. 231 of the year 1996 concerning some stipulations regulating the employment of Egyptians by foreign entities = قانون رقم 76 لسنة 2016 بتعديل بعض أحكام القانون رقم 231 لسنة 1996 ببعض الأحكام الخاصة بتنظيم عمل المصريين لدى جهات أجنبية. (2025)
Law no. 76 of the year 2016 on amending certain provisions of law no. 231 of the year 1996 concerning some stipulations regulating the employment of Egyptians by foreign entities قانون رقم 76 لسنة 2016 بتعديل بعض أحكام القانون رقم 231 لسنة 1996 ببعض الأحكام الخاصة بتنظيم عمل المصريين لدى جهات أجنبية